2006
DOI: 10.1515/cclm.2006.039
|View full text |Cite
|
Sign up to set email alerts
|

Nitration of human plasminogen by RAW 264.7 macrophages reduces streptokinase-induced plasmin activity

Abstract: Despite many years of study, clinical trials of new drugs to prevent thrombosis have often been disappointing. Part of the problem lies in our incomplete understanding of the regulation of plasminogen activation and/or inhibition in vivo. We have previously shown that in vitro nitration of plasminogen in plasma by peroxynitrite resulted in decreased plasmin activity. We hypothesized that macrophages may be agents of plasminogen nitration and designed this study to prove this hypothesis. We first better charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…This is an essential homeostatic system that controls the balance between coagulation and fibrinolysis (Baruah et al, 2006). We have shown previously that plasminogen is sensitive to inactivation by nitrogen species attacking Tyr residues (Hathuc et al, 2006;Gugliucci and Menini, 2003). Since plasminogen lacks critical Lys or Cys residues, we included it in our experiments to rule out non-specific effects of acrolein or homocysteine thiolactone on AT (denaturing, heavy aggregate formation etc).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an essential homeostatic system that controls the balance between coagulation and fibrinolysis (Baruah et al, 2006). We have shown previously that plasminogen is sensitive to inactivation by nitrogen species attacking Tyr residues (Hathuc et al, 2006;Gugliucci and Menini, 2003). Since plasminogen lacks critical Lys or Cys residues, we included it in our experiments to rule out non-specific effects of acrolein or homocysteine thiolactone on AT (denaturing, heavy aggregate formation etc).…”
Section: Discussionmentioning
confidence: 99%
“…Thrombosis producing myocardial infarction and stroke is the final common pathway of atherosclerosis and also a complication of many other chronic diseases such as diabetes and renal failure (Bick, 1994;Nieuwdorp et al, 2005). Two key protein systems that control the delicate balance between coagulation and fibrinolysis are antithrombin and plasminogen and both have been previously shown to be inhibited by carbonyl or nitrosative stress (Thomas, 2001;Sakurai et al, 1988;Hathuc et al, 2006;Gugliucci and Menini, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The first report suggesting the possibility of ROS generation in platelets was published in 1977 [ 30 ]. Since then, it has been found that oxidative stress influence functions of various elements of the haemostatic system, including modulation of platelet activity [ 31 33 ], changes in fibrinogen polymerization [ 34 , 35 ] as well as impairment of fibrinolysis [ 36 , 37 ]. Activation of blood platelets initiates conformational changes in platelet membrane receptors and numerous intra-platelet processes such as exocytosis of granules, secretion of vasoactive mediators, and cytoskeleton reorganization.…”
Section: Discussionmentioning
confidence: 99%
“…oxidative stress), results obtained by Lind et al [3] demonstrated the sensitivity of plasmin for oxidative inactivation. Studies of Hathuc et al [4], with the use of SIN-1, showed an evident correlation between plasmin inhibition and tyrosine nitration. In other experiments of those authors, after 24 h of incubation of plasminogen with macrophages, about 60% decrease of plasmin activity associated with the increased nitration of tyrosine residues in plasminogen molecule, was observed.…”
Section: Introductionmentioning
confidence: 90%